Synthesis and Expression of Tissue Factor Pathway Inhibitor by Serum-stimulated Fibroblasts, Vascular Smooth Muscle Cells and Cardiac Myocytes - Bajaj, M. S.; Steer, S.; Kuppuswamy, M. N.; Kisiel, W.; Bajaj, S. P. (Thrombosis and Haemostasis, 1999)
Tissue factor pathway inhibitor (TFPI) plays an important role in regulating tissue factor (TF)-initiated blood coagulation. Since serum stimulation of fibroblasts, vascular smooth muscle cells and cardiac myocytes in culture increases the expression of TF mRNA and antigen (Ag) in these cells, we hypothesized that serum may also induce increased synthesis of TFPI in these cells to regulate the TF-induced extravascular clotting at an injury site. To test this concept, we used primary isolates of the following human cell types – fetal and adult lung fibroblasts, pulmonary and aortic smooth muscle cells, and cardiac myocytes. Serum-stimulation of these cells resulted in an increased expression of TF mRNA and Ag (8 to10-fold). Upon serum stimulation, expression of TFPI mRNA and Ag was also increased in these cells. However, the increase in TFPI-Ag (6 to 8-fold) was significantly greater than the TFPI mRNA (2 to 3-fold). Notably, increased expression of TFPI persisted after the TF expression had declined. Further, increased synthesis of TFPI initially led to the saturation of heparin-releasable binding sites. TFPI-Ag was detected by Western blotting, 35S-metabolic labeling and activity assays on the conditioned media, heparin-released material from cells, and in cell lysates. TFPI-Ag was also detected by immunofluorescence staining of cells. Actinomycin D partially whereas cycloheximide completely prevented the serum-induced increased expression of TFPI synthesis by these cells, suggesting control primarily at the translational but some at the transcriptional level as well. The Mr of undegraded TFPI in all cases was ~45 kDa and was of full length. TFPI synthesized locally by fibroblasts, vascular smooth muscle cells and cardiac myocytes could play a significant role in regulating TF-initiated extravascular clotting especially since plasma TFPI that may be available at the injury site lacks a portion of the carboxyl segment and is a less efficient inhibitor.
Keywords: Tissue factor; TFPI; fibroblasts; smooth muscle cells; myocytes